2019
DOI: 10.5194/acp-19-13591-2019
|View full text |Cite
|
Sign up to set email alerts
|

Secondary organic aerosol formation from photooxidation of furan: effects of NO<sub><i>x</i></sub> and humidity

Abstract: Abstract. Atmospheric furan is a primary and secondary pollutant in the atmosphere, and its emission contributes to the formation of ultrafine particles. We investigate the effects of NOx level and humidity on the formation of secondary organic aerosol (SOA) generated from the photooxidation of furan in the presence of NaCl seed particles. SOA mass concentration and yield were determined under different NOx and humidity levels. A significant difference is observed both in the variation of SOA mass concentratio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 96 publications
(125 reference statements)
0
14
0
Order By: Relevance
“…Alvarez et al 22 reported that OH-initiated oxidation of furans can produce a large set of unsaturated 1,4-dicarbonyls in the aerosol phase, while Joo et al 23 suggested that nitrate radical (NO 3 )-initiated oxidation of 3methylfuran can not only generate a variety of carbonyls but also dimers and oligomers. Strollo and Ziemann 24 indicated that oligomerization is the key to SOA formation during 3methylfuran daytime oxidation, while Jiang et al 25 highlighted the potentially important role of multifunctional dihydroxyl organonitrate products in SOA formation in the furan−NO x − NaCl system. However, our understanding of the chemical composition of reaction products in furan oxidations is still limited, making it difficult to evaluate the physicochemical properties of furan SOA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Alvarez et al 22 reported that OH-initiated oxidation of furans can produce a large set of unsaturated 1,4-dicarbonyls in the aerosol phase, while Joo et al 23 suggested that nitrate radical (NO 3 )-initiated oxidation of 3methylfuran can not only generate a variety of carbonyls but also dimers and oligomers. Strollo and Ziemann 24 indicated that oligomerization is the key to SOA formation during 3methylfuran daytime oxidation, while Jiang et al 25 highlighted the potentially important role of multifunctional dihydroxyl organonitrate products in SOA formation in the furan−NO x − NaCl system. However, our understanding of the chemical composition of reaction products in furan oxidations is still limited, making it difficult to evaluate the physicochemical properties of furan SOA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Figure 3b gives an example for the furanic group that the precursors (such as furan, methyl-furan, and furfural) decreased in light but not in dark experiments (Figure S6). Furanic compounds have been widely reported to be the main precursors of SOA in biomass (Hartikainen et al, 2018) and solid fuel burning emission (Ahern et al, 2019), and could have an SOA yield of up to 5% (Jiang et al, 2019). Table S2 (in red) summarized all gaseous precursors, including some aromatics (benzene, toluene, and C8-aromatics), carbonyl (acrolein, MVK, and 3-methyl-3-butene-2-one), and phenolic (phenol and cresol for SM) compounds.…”
Section: Evolution Of Organic Aerosols and Gasesmentioning
confidence: 99%
“…RO radicals generally fragment into smaller more volatile products, resulting in small amounts of SOA (Sarrafzadeh et al, 2016). It should also be noted that the presence of sufficient seed surface area at the start of the reaction largely suppresses the effects of vapour wall losses of low-volatility compounds, including multifunctional nitrates (Schwantes et al, 2019), which promotes their partition into the particle phase and increases the SOA mass concentration (Jiang, 2019).…”
Section: Effect Of Nox and Rhmentioning
confidence: 99%
“…These compounds can be absorbed into the humid surface of the hygroscopic SOA at high RH, contributing to the formation of low volatility products and increasing the SOA mass yields. Moreover, these hydrophilic functional groups at the SOA surface, could also absorb the water molecules and hence, the produced SOA could partition into new wet particles (Jiang et al, 2019).…”
Section: Effect Of Nox and Rhmentioning
confidence: 99%
See 1 more Smart Citation